Projecting the sexual minority population: methods, data, and illustrative projections for Australia - Wilson, Tom; Temple, Jeromey; Lyons, Anthony (My University, 2021)
BACKGROUND: Attitudes to sexual minorities have undergone a transformation in many Western countries in recent decades. With much greater public acceptance, and an increase in policies and legislation to support equality and outlaw discrimination, the need for population statistics on sexual minority populations has grown. However, such statistics remain rare; only a few sets of population estimates have been produced in a small number of countries, and there are no population projections of which we are aware. OBJECTIVE: The aims of this paper are to introduce a model for producing projections of a national population by sexual identity, suggest ways in which data and conceptual limitations can be handled, and present illustrative population projections for Australia. METHODS: An adapted multistate cohort-component is described, along with various data sources and approaches for preparing plausible projection assumptions. Two illustrative scenarios for the future of Australia’s sexual minority population over the 2016-2041 period are presented. RESULTS: According to the selected scenarios, Australia’s sexual minority population is projected to increase rapidly over the coming decades, rising from 0.65 million in 2016 to between 1.25 and 1.57 million by 2041. This growth is generated by sexual minority cohort flow – the gradual replacement of cohorts with lower sexual minority identification proportions by those with the higher proportions – and identification change. The overall share of the population identifying with a sexual minority identity is likely to increase. CONCLUSION: Although the projections remain illustrative and approximate, the likely coming growth of the sexual minority population signals multiple social, health, and economic policy implications ahead. CONTRIBUTION: The paper presents a novel projection method and example projections of an under-researched and stigmatised population.
Demographic Research
Keywords: Gender